Pelatihan Pemanfaatan Personal Branding dalam Digital Marketing untuk UMKM - Friantin, Siti Hayati Efi; Putri, Ika Swasti (TAAWUN, 2023)
The COVID-19 pandemic has been declared reduced, although maintaining health protocols is still applied. The logical consequence of the ongoing needs of life, many business sectors have started to rise and start their business again. However, large-scale businesses have not recovered because during the pandemic many of them collapsed, went bankrupt and laid off many of their employees. It was SMEs (Micro, Small and Medium Enterprises) that could survive. However, to survive more safely, creative and innovative ideas are needed to reduce costs to be efficient. One way for creative and innovative ideas is to do marketing through the internet or often referred to as digital marketing. Digital marketing is now being popularly introduced and used in various business sectors. Digital marketing cuts costs a lot, including space, time, energy and promotional costs. Even people can sell without leaving the house. Therefore, this community service activity is interested in conducting training and mentoring for MSMEs with the theme "Training and Assistance in the Use of Personal Branding in Digital Marketing for MSMEs in Gilingan Village, Banjarsari District, Surakarta". Through this community service activity, we will provide a solution to this problem by providing HR Quality Improvement Training in Branding Strategies Through Digital Marketing for MSMEs. This service activity is carried out using a personal and group approach according to the needs and abilities of the participants and direct training at 6-month intervals. with the target output of scientific publications/print media (online). This community service activity has been carried out routinely and is part of the Tri Dharma of Higher Education: Education, Research and Community Service Activities